Product quality in a simple OLG model of scientific competition - Max Albert (Philipps-University Marburg, Faculty of Business Administration and Economics, 2008)
Using a simple OLG model where the research output of one generation provides inputs for the next, the paper explains how quality standards can become established in scientific competition. Researchers seek status, which they get if their results are used by the next generation. Quality is hereditary in the sense that input quality affects output quality. Hereditary quality allows for simple coordination on quality standards.
Keywords: D02; L31; O31; 330; economics of science; methodology of economics; product quality; quality standards; scientific competition